PENGARUH KECERDASAN EMOSIONAL DAN PERILAKU BELAJAR TERHADAP PEMAHAMAN AKUNTANSI (Studi pada Mahasiswa Akuntansi Program S1 Universitas Brawijaya) - Ahmad Rizal Jayadi; Lilik Purwanti (Jurnal Ilmiah Mahasiswa FEB, 2013)
This research aims  to examine impact of emotional intelligence  that is measured by self understanding, self control, motivation, empathy, and social ability, and learning behavior that is measured by aspects of the habit following the lesson, the habit of reading books, visiting libraries, and habits for exams whereas accounting understanding was measured by score of accounting subjects. Research sample is 80 respondents. Data analysis method is multiple regression. Result of examination indicates that  hypothesis 1 which stated that  emotional intelligence  by self understanding, self control, motivation, empathy, and social ability  significantly influence the interest of  accounting understanding. Hypothesis 2 which stated that learning behavior measured by aspects of the habit following the lesson, the habit of reading books, visiting libraries, and habits for exams significantly influence the interest of accounting understanding. Hypothesis 3 which stated that  emotional intelligence  and  learning behavior in a together influence the interest of accounting understanding. Keywords:  Emotional  Intelligence,  Learning Behavior, Accounting Understanding